2018
DOI: 10.5114/pjr.2018.75870
|View full text |Cite
|
Sign up to set email alerts
|

The role of diffusion and perfusion magnetic resonance imaging in differentiation of haemangioblastomas and pilocytic astrocytomas

Abstract: PurposeHaemangioblastomas (HABLs) and pilocytic astrocytomas (PAs) are brain tumours presenting similar appearance and location in conventional magnetic resonance (MR) imaging. The purpose of our study was to determine whether a detailed analysis of diffusion (DWI) and perfusion (PWI) characteristics can be useful in preoperative differentiation of these tumours.Material and methodsThe study group consisted of biopsy proven six HABLs and six PAs, which underwent preoperative standard MR examinations including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The calculated ADC values from the peritumoral areas of hemangioblastoma were higher than pilocytic astrocytoma. According the study of Malgorzata et al (22) the intratumoral mean and minimum ADC values of the hemangioblastoma and the pilocytic astrocytoma were close to each other. This may support the usability of peritumoral ADC values rather than intratumoral ADC values for the differentiation between two tumor groups in childhood.…”
Section: Discussionmentioning
confidence: 83%
“…The calculated ADC values from the peritumoral areas of hemangioblastoma were higher than pilocytic astrocytoma. According the study of Malgorzata et al (22) the intratumoral mean and minimum ADC values of the hemangioblastoma and the pilocytic astrocytoma were close to each other. This may support the usability of peritumoral ADC values rather than intratumoral ADC values for the differentiation between two tumor groups in childhood.…”
Section: Discussionmentioning
confidence: 83%
“…Advanced MRI techniques can help to differentiate PAs and Mets from HBs. HBs often show prominent rCBV values, increased ADC values, and high Lip/Lac without necrosis, while PAs show mildly increased rCBV ratio ranges of 1.40–1.82, 37 39 iso to increased ADC value ranges of 1.11–1.64 × 10 −3 mm 2 /s, 26 , 37 39 and high Lip/Lac without necrosis. 8 , 32 , 33 Finally, Mets show mild to prominent increased rCBV ratio ranges of 2.55–10.80, 9 , 11 , 12 , 40 45 decreased to mildly increased ADC values ranges of 0.79–1.35 × 10 −3 mm 2 /s, 9 , 11 , 12 , 41 , 42 , 44 and high Lip/Lac with necrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 25 In contrast, increased ADC has been reported in cerebellar HBs, with values in the range of 1.27–1.55 × 10 −3 mm 2 /s. 9 11 , 26 HBs are characterized by the presence of a network of capillary-like channels separated by stromal cells. The increased ADC values could be attributed to the high vascular spaces of capillaries as well as low cellular attenuation in HBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of rCBV values in differentiating PAs from high-grade gliomas have also been recognized in the literature. However, these investigations have not separated the STPAs and STEEs from those infratentorialy and intraventricularly, or not taken the STEEs as high-grade gliomas into consideration (25,27,34,38,39). Perfusion-related research about unique STPAs and STEEs has only been reported in limited case reports as far as we know (22,24,25).…”
Section: Discussionmentioning
confidence: 99%